Depth-Resolved Distribution of Particle-Attached and Free-Living Bacterial Communities in the Water Column of the New Britain Trench - Liu, Rulong; Wang, Li; Liu, Qianfeng; Wang, Zixuan; Li, Zhenzhen; Fang, Jiasong; Zhang, Li; Luo, Min (Frontiers in Microbiology, 2018)
Particle-attached (PA) and free-living (FL) microorganisms play significant but different roles in mineralization of organic matter (OM) in the ocean. Currently, little is known about PA and FL microbial communities in bathyal and abyssal pelagic waters, and understanding of their diversity and distribution in the water column and their interactions with environmental factors in the trench area is limited. We investigated for the first time the variations of abundance and diversities of the PA and FL bacterial communities in the epi-, bathy-, and abyssopelagic zones of the New Britain Trench (NBT). The PA communities showed decreasing species richness but increasing relative abundance with depth, suggesting the increasing ecological significance of the PA bacteria in the deep ocean. The abundance and diversity of PA and FL bacterial communities in the NBT water column appeared to be shaped by different sets of environment factors, which might be related to different micro-niches of the two communities. Analysis on species distribution suggested that the differences between PA and FL bacteria communities mainly resulted from the different relative abundance of the “shared taxa” in the two types of communities. These findings provide valuable information for understanding the relative ecological roles of the PA and FL bacterial communities and their interactions with environmental factors in different pelagic zones along the vertical profile of the NBT water column.